Enhancing Biology Education: Effective Methods for Utilizing Laboratory Classes (Journal of Pedagogical Inventions and Practices, 2023)
Laboratory classes play a crucial role in biology education, providing students with hands-on experiences and opportunities to apply theoretical concepts in practical settings. This scientific article explores various methods for using laboratory classes in the teaching of biology. It discusses the benefits of laboratory classes, the design of effective experiments, strategies for fostering inquiry-based learning, and the integration of technology in laboratory instruction. The article also addresses the challenges associated with laboratory classes and provides recommendations for enhancing their effectiveness in promoting student learning and engagement in biology education